The first ABO-incompatible kidney transplantation performed in Portugal - Barreto, P. (2015)
Kidney transplantation is the optimal treatment of end-stage renal disease (ESRD) improving survival and quality of life for most recipients. In our country, potential living donors have been refused due to the ABO incompatibility barrier. However, ABO -incompatible living donor kidney transplant is presently common practice in several countries with good outcomes. The authors describe a case of a 49-year-old female patient, with chronic kidney disease due to autosomal dominant polycystic kidney disease, who had started haemodialysis 10 months before and with blood group O. The living donor was a 53-year-old sister with blood group B. The desensitization protocol was based on rituximab and plasmapheresis. The induction protocol used was basiliximab, tacrolimus, mofetil mycophenolate and metilprednisolone. Five days post -transplant she presented a normal graft function that remained during the eight months follow -up. This case reveals the first ABO incompatible living donor kidney transplant performed in Portugal with excellent outcome